Budget Deficit, National Debt, and Government Spending: Is Now the Right Time to Cut Deficit and Reduce National Debt? - Sara Aliabadi; Alireza Dorestani; Aijana Abdyldaeva (Journal of Accounting, Business and Management (JABM), 2011)
The current economic downturn has raised the question of whether the national debt is too large to continue spending or whether it is impossible to stimulate the economy without increasing national debt. The paper tempts to provide arguments for and against budget deficit and investigates the effects of freezing government spending on unemployment and Consumer Price Index (CPI). In this study we posit that the direction of association between government spending and unemployment rate and government spending and CPI are not theoretically determinable. Therefore, in this study we examine the above associations. Government budget deficit and national debt has an important effect on current and future generations. Our results show that opposing factors cancel out each other and there is no significant association between government spending and unemployment rate and government spending and CPI. We show and conclude that the current state of the economy calls for immediately cutting the government spending to reduce budget deficit and national debt.